Design and Implementation of a VBA-Based Uniform Inventory Accounting System: A Qualitative Case Study at SMA El Fitra Bandung - Nadiyah Nur Hasanah (Penerbit Goodwood, 2024)
Purpose: Many educational institutions in Indonesia still use manual inventory recording, leading to recording errors, stock discrepancies, slow data retrieval, and weak financial control. This study develops a Visual Basic for Applications (VBA) based inventory accounting system in Microsoft Excel for SMA El Fitra Bandung to replace its handwritten school uniform inventory records.Research Methodology: A qualitative case study was conducted using unstructured interviews, direct observation, and documentation of inventory records. The system was developed using the five-stage waterfall method and implemented in Microsoft Excel with VBA Macro, featuring five modules: Main Menu, Item Data, Incoming Goods, Outgoing Goods, and Save/Exit.Results: Five system trials resulted in three successful tests, while two coding errors were resolved during maintenance. The final system accurately managed inventory transactions, generated reports, and improved efficiency, accuracy, accessibility, and data security.Conclusions: The VBA-based system effectively replaced manual inventory recording, with the Waterfall method ensuring structured development and implementation.Limitations: The system is limited to inventory recording and requires staff VBA competency and proper supplier receipt management for sustainable operation.Contributions: This study offers a replicable VBA-based inventory system for small institutions, contributing to accounting system design and institutional informatics.